Comparative analysis of maximum consume of oxygen and the lapsing of intensity of aerobic training: ergoespirometric versus conventional ergometric test - Costa, Francisco Carlos (2011)
Compare the maximum consumption of oxygen estimated (VO2maxE) by the formula of ACSM (2000) in a conventional ergometric test with the maximum consumption of oxygen obtained in an ergoespirometric test, as well as compare the inferior and superior limits of lapsing of aerobic training intensity determined by the ergometric test (50% and 85% VO2maxE) with of lapsing of aerobic training intensity obtained by the ergoespirometric test: anaerobic limit and respiratory compensation point, in young sedentary adults. 11 individuals (24 years) were submitted to gradual ergoespirometric test until the exhaustion so VO2max, VO2 in anaerobic limit and VO2 in respiratory compensation point were measured, apart from measuring the speed and inclination obtained at the end of each test in order to determine the lapsing of aerobic training intensity of 50% VO2maxE and 85% VO2maxE. The VO2maxE obtained at the ergometric test was 52.31 ml/Kg/min and the VO2max measured at the ergoespirometric test was 43.18 ml/Kg/min. The superior limit of exercise intensity (85% VO2maxE = 44.46 ml/Kg/min) proposed by the ACSM (2000), when compared to the ergoespirometric test (VO2PCR = 34.31 ml/Kg/min) revealed a significant difference. The VO2maxE over estimated the measure obtained by the ergoespirometric test. The inferior limit of VO2through the indirect lapsing of aerobic training is similar with the anaerobic limit, while the superior limit overestimates the respiratory compensation point (p-<0.05).